Effect of Salt Concentration on the Preparation and Quality of Lemon Pickle (Nimki) - Acharya, Anubha; Pradhananga, Mahalaxmi (Himalayan Journal of Science and Technology, 2021)
The main aim was to study the effect of dry salting (0, 5, 10, 15, and 20% by weight) on the quality of lemon pickle. The samples were analyzed for microbial profile (Yeast, mold) and chemical characteristics at 15 days intervals till 90 days and the organoleptic quality of the product was evaluated after 90 days of storage. The data were statistically analyzed using two-way ANOVA (no blocking) at a 5% level of significance results showed that titratable acidity decreased with storage time till 60 days and remained constant thereafter at all levels of salt concentrations; Vitamin C remained fairly constant at all levels of salt concentrations over the storage periods whereas it decreased steadily during storage in the control sample (i.e. 0%); Mold count was nil at 15 days for all the level of salt except control and 5% concentration and Yeast count increased with storage time regardless of the salt% used in a lemon pickle. The optimized salt concentration for the preservation of lemon was found to be 15% salt which was the best product through sensory evaluation with the least microbial load and having appreciable sensory attributes and good vitamin C retention.